Literature Review: Perbandingan Penurunan Berat Badan pada Penggunaan Insulin Dulaglutide dengan Insulin Rekombinan Glargine pada Diabetes Mellitus Tipe 2 - Nurfirah Mubarok; Salman Salman (Jurnal Sehat Mandiri, 2024)
The widespread diabetes epidemic throughout the world has the potential to have a devastating impact on the development of health systems and economies in developing countries, both in terms of direct health care costs as well as lost work time and disability. This study aims to investigate and compare the weight loss effects between the use of insulin dulaglutide and recombinant insulin glargine in patients with type 2 diabetes mellitus. The method for writing this article is to use the literature review method. The results of a critical analysis of scientific literature over the last ten years (2014 – 2024) strengthen understanding of the differences in clinical efficacy of these two types of insulin. Through a synthesis of empirical evidence, this review presents a comprehensive picture of the ability of each insulin to treat weight loss. Conclusion: Dulaglutide insulin is proven to be more effective for weight loss compared to recombinant insulin Glargine, however dulaglutide insulin has higher gastrointestinal side effects compared to insulin glargine. It is recommended to try to dig up information about similar cases, so that it is hoped that therapy for patients suffering from diabetes can be given maximum treatment.